2020
DOI: 10.1002/aocs.12416
|View full text |Cite
|
Sign up to set email alerts
|

Cold Plasma Treatment of Soybean Oil with Hydrogen Gas

Abstract: High‐voltage atmospheric cold plasma (HVACP) treatment generates reactive gas species that induce inter‐ and intramolecular reactions in soybean oil. The goal of this study is to analyze the effect of HVACP treatment on the chemical structure of soybean oil in a hydrogen gas environment at atmospheric pressure. HVACP was used to treat soybean oil (15 g) for up to 6 hours by triplicate. Plasma‐generated reactive gas species interact with the sample, producing three distinct fractions identified as a liquid, gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…At 90%He and 10%H 2 , all peaks of He species were clearly detected at 336, 356, 388, 501, 587, 667, 706 and 727.5 nm while only one peak of H 2 species appeared which was H α at 656.3 nm representing hydrogen atom excitation. This was related to the characteristic of cold plasma presented in the study of El-Zeer et al 49 and mentioned in Yepez et al 46 ’s work that cold plasma consisted mostly of hydrogen radicals responding in the reaction. For the case of 20%He and 80%H 2 , the plasma color was visually observed to became brighter/lighter, having a more whitish tone as shown in supplementary materials Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…At 90%He and 10%H 2 , all peaks of He species were clearly detected at 336, 356, 388, 501, 587, 667, 706 and 727.5 nm while only one peak of H 2 species appeared which was H α at 656.3 nm representing hydrogen atom excitation. This was related to the characteristic of cold plasma presented in the study of El-Zeer et al 49 and mentioned in Yepez et al 46 ’s work that cold plasma consisted mostly of hydrogen radicals responding in the reaction. For the case of 20%He and 80%H 2 , the plasma color was visually observed to became brighter/lighter, having a more whitish tone as shown in supplementary materials Fig.…”
Section: Resultsmentioning
confidence: 76%
“…In a cold hydrogen plasma, it was reported that the generated reactive species were H + , H 3+ and H • of 0.0001%, 0.1%, and 1%, respectively. The system was rich in H • , so they should most participate in the hydrogenation of FAME 46 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the linoleic acid (C18:2) has one bis‐allylic site at C‐11 due to their double bonds at Δ9 and Δ12 (C18:2 cis 9, cis 12). H + can react with the bis‐allylic site resulting in the double bond shifting with the formation of conjugated linoleic acids, trans 10, cis 12 and cis 9, trans 11 65 . This mechanism can occur with linolenic acid (C18:3) as well.…”
Section: Resultsmentioning
confidence: 99%
“…Soybean oil treated with a modified atmosphere of nitrogenhydrogen gas was treated with high voltage ACP to increase the oil viscosity and change the fatty acid composition. The effect of ACP treatment was focused on the reduction of polyunsaturated fatty acids and increment of saturated fatty acids without the formation of the undesired trans isomers [84,85]. Changes in the chemical structure of vegetable oil are desired for applications such as frying and formulations that require provide specific oxidation stability or higher melting points in food products.…”
Section: Cold Plasma In Food Processingmentioning
confidence: 99%